2016
DOI: 10.1051/matecconf/20179001035
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic flux gradient observation during fatigue crack propagation: A case study of SAE 1045 carbon steel used for automotive transmission parts

Abstract: Abstract. The objective of this study is to evaluate the application of the metal magnetic memory (MMM) technique for investigations on fatigue crack propagation in a ferromagnetic material. Fatigue failure caused by stress concentration is serious in practical engineering. However, early fatigue damages cannot be detected by using traditional nondestructive testing (NDT) methods. Therefore this paper study about NDT method called metal magnetic memory (MMM) that has potentials for evaluating the fatigue damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…MMM exhibits high possibility to classify and estimate fatigue crack damage and remaining life (Ahmad et al, 2016). Ahmad suggested that the actual position of a crack can be identified with the utilisation of dH/dx (Ahmad et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…MMM exhibits high possibility to classify and estimate fatigue crack damage and remaining life (Ahmad et al, 2016). Ahmad suggested that the actual position of a crack can be identified with the utilisation of dH/dx (Ahmad et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…e correlation analysis of the magnetic memory signal with the degree of stress concentration was carried out [5], revealing the variation rule of magnetic memory signal under quasi-static and fatigue loads [6,7] and describing the effects of different initial magnetic states, external magnetic field, and temperature on the magnetic signal [8,9]. In addition, magnetic features are also used to predict fatigue crack propagation paths of remanufactured components [10]. By extracting magnetic features such as multidimensional signals [11], magnetic flux leakage parameters [12], and fuzzy entropy [13], the research on structural failure prediction [14], residual stress evaluation, fatigue life characterization, and cumulative plastic damage quantification of ferromagnetic components is carried out [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…MMM provides a high tendency to measure fatigue crack damage and predict remaining life [14]. The usage of dH(y)/dx has been suggested by Ahmad et al [15] to detect the real position of a crack.…”
Section: Introductionmentioning
confidence: 99%